POSISI, TANTANGAN, DAN PROSPEK BAGI INDONESIA DALAM SISTEM PENYELESAIAN SENGKETA WTO - F. D. Sitanggang, Dyan (Veritas et Justitia, 2017)
The World Trade Organization (WTO) as the sole universal organization managing global trade between member-states has develop a dispute settlement mechanism to deal with disagreement related to the interpretation and/or implementation of reciprocal rights and duties in the economic field. However, the effectiveness of this system hinges on compliance of states to decisions reached.  Compliance in its turn are influenced by how parties to a dispute value the justness or equity of the final settlement.  This paper discusses WTO Dispute Settlement Understanding (DSU) and how Indonesia perceived and utilizes this forum to further its national interest.